The impact of empowering employees on administrative creativity: An applied study on the employees of the non-profit sector in Buraida, Kingdom of Saudi Arabia (International Journal of Financial, Administrative and Economic Sciences, 2026)
The study aims to identify the impact of empowerment in its dimensions (delegation of authority - training - work teams -motivation) on the administrative creativity of workers in non-profit organizations in the city of Buraidah, Saudi Arabia. In order to achieve the objectives of the study, the researcher used a descriptive analytical method to describe the phenomena as they are in reality. In the study, the researcher will rely on two types of data: primary data, which are represented in the field study and what it contains of data and information related to the study, and secondary data such as books, articles, reports, research studies related to the subject of the study and its variables.. The questionnaire will be used as a tool for the field study after verifying its validity and reliability. The study community consists of all non-profit organizations in the city of Buraidah in the Kingdom of Saudi Arabia, which are (64) organizations, and a random sample of estimated (47) non-profit organizations was selected, taking into account their diversity of where its size and the nature of its community activity when selecting the sample. Based on the results of the field study, the researcher hopes to get acquainted with the quality and nature of the challenges facing the empowerment process with its dimensions on the administrative creativity of workers in non-profit organizations in Buraidah; To present a set of recommendations that may contribute to improving their performance and achieving their goals efficiently and effectively, which has become an urgent requirement in accordance with the  2030 vision.
Keywords: Empowering Employees; Administrative Creativity; the Non-Profit Sector